Sociology in Iran - Jamil Farooqui (International Institute of Islamic Thought, 1993)
The book, with the help of empirical data, provides valuable information about the development of sociology as a discipline in Iran. It explains how the discipline was introduced in one of the colleges of Tehran in 1946 and gradually, over a span of twenty-five years, became a popular subject of teaching and research. The number of qualified students and staff is also steadily increasing. But more importantly, Iran now has a unifonn B.A. degree program consisting of 144 credit hours in eight 17-week semesters. Five categories of courses related to different areas and subareas are provided: general, base, main, elective, and specialized courses. In all of these courses, sociology and its various branches are mentioned. The M.A. degree program has been developed with the intention of preparing a competent cadre of future teachers for the higher centers of learning. The program is similar to that found in European and American universities, with the exception of courses on the social thought of Muslim thinkers and the social ideas of Muslim philosophers, theologians, intellectuals, and historians. A doctoral program has also been introduced for training university faculty and researchers. The program requires thirty credit hours over a period of seven semesters. Out of these credit hours, twenty-two are required courses ...